Electrochemical Detection of Hydrogen Peroxide at High Concentrations Using Hastelloy G35 Electrode - Alboull, Ala'a Mhmoued Abdllh (Langmuir : the ACS journal of surfaces and colloids, 2025)
The detection of hydrogen peroxide (H2O2) at elevated concentrations while eliminating oxygen interference presents a significant challenge. Nickel-based stainless steel, such as Hastelloy G35, has shown excellent corrosion resistance. However, it has never been used in electroanalysis. In this study, the electrochemical analysis of H2O2 was conducted for the first time using nickel-based stainless steel electrode. The Hastelloy G35 electrode exhibited a very wide linear range from 1 up to 1000 mM and a detection limit of 0.0135 mM. The method is free from interference by oxygen. This method effectively detected H2O2 in skin wound wash solutions with excellent recoveries. The excellent performance of this method enhances its applicability in various fields, including industrial processes, environmental monitoring, and analytical chemistry, where quantifying concentrated H2O2 is of utmost importance. It shows that nickel-based stainless steel is promising for electroanalysis